1986
DOI: 10.1152/jappl.1986.61.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal and tympanic temperature responses to core blood temperature changes during hyperthermia

Abstract: Esophageal, rectal, tympanic, and central blood temperature, i.e., pulmonary artery and aortic arch, were recorded in three patients during iatrogenic whole-body hyperthermia for the treatment of advanced malignant metastatic cancer. Aortic temperature closely followed changes in pulmonary arterial temperature, with an average delay time of 27 s. Esophageal temperature reflected quantitatively and more quickly (avg lag time, 80 s) the temperature changes in the pulmonary artery than tympanic membrane temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 0 publications
2
54
0
1
Order By: Relevance
“…Thus, measuring core temperature through the tympanic membrane vs. the rectum and esophagus may produce different results. Studies suggest that T TY may underestimate core temperature by 0.3-0.6 °C relative to esophageal or rectal tem perature (Jensen et al, 2000;Roth et al, 1996;Shiraki et al, 1986;Yeo and Scarbough, 1996). However, Newsham et al (2002) have also shown a strong correlation between T TY and rectal temperature.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Thus, measuring core temperature through the tympanic membrane vs. the rectum and esophagus may produce different results. Studies suggest that T TY may underestimate core temperature by 0.3-0.6 °C relative to esophageal or rectal tem perature (Jensen et al, 2000;Roth et al, 1996;Shiraki et al, 1986;Yeo and Scarbough, 1996). However, Newsham et al (2002) have also shown a strong correlation between T TY and rectal temperature.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…http://dx.doi.org/10.4040/jkan.2012.42.3.424 www.kan.or.kr 의 표준이 된다 (Shiraki, Konda, & Sagawa, 1986) (Sohng et al, 2009;Shiraki et al, 1986;Lee & Jung, 1995 Potter, Perry, & Stockert, 2010). 이마체 온은 직장체온이나 고막체온보다 더 정확하고 (Greenes & Fleisher, 2001), 아동의 발열상태를 잘 감별해 내며 (Siberry, Diener -West, Schappell, & Karron, 2002), 구강체온보다 더 정확할 뿐 아니라 폐동 맥은 물론 식도의 심부체온에 필적한다는 보고가 있다 (Carroll, Finn, Judge, Gill, & Sawyer, 2004).…”
unclassified
“…Other modes of core temperature measurement include esophageal temperature measurement using a purposedesigned thermistor probe (6,7) and rectal temperature measurement by means of a thermistor probe deep in the rectum (3,8). In the last few decades, there has been considerable interest in infrared ear-based thermometry, a method based on the principle of radiation of infrared energy by the tympanic membrane in proportion to its temperature.…”
mentioning
confidence: 99%